DNA Delivery and Genomic Integration into Mammalian Target Cells through Type IV A and B Secretion Systems of Human Pathogens - Guzmán-Herrador, Dolores L.; Steiner, Samuel; Alperi, Anabel; González-Prieto, Coral; Roy, Craig R.; Llosa, Matxalen (Frontiers in Microbiology, 2017)
We explore the potential of bacterial secretion systems as tools for genomic modification of human cells. We previously showed that foreign DNA can be introduced into human cells through the Type IV A secretion system of the human pathogen Bartonella henselae. Moreover, the DNA is delivered covalently attached to the conjugative relaxase TrwC, which promotes its integration into the recipient genome. In this work, we report that this tool can be adapted to other target cells by using different relaxases and secretion systems. The promiscuous relaxase MobA from plasmid RSF1010 can be used to deliver DNA into human cells with higher efficiency than TrwC. MobA also promotes DNA integration, albeit at lower rates than TrwC. Notably, we report that DNA transfer to human cells can also take place through the Type IV secretion system of two intracellular human pathogens, Legionella pneumophila and Coxiella burnetii, which code for a distantly related Dot/Icm Type IV B secretion system. This suggests that DNA transfer could be an intrinsic ability of this family of secretion systems, expanding the range of target human cells. Further analysis of the DNA transfer process showed that recruitment of MobA by Dot/Icm was dependent on the IcmSW chaperone, which may explain the higher DNA transfer rates obtained. Finally, we observed that the presence of MobA negatively affected the intracellular replication of C. burnetii, suggesting an interference with Dot/Icm translocation of virulence factors.